American Novelists in Italy : The Discoverers, Allston to James - Wright, Nathalia (University of Pennsylvania Press, 2016)
This is a study of the effect of their travels in Italy on thirteen American writers, among them Washington Irving, Nathaniel Hawthorne, Harriet Beecher Stowe, W. D. Howells, and Henry James. Dr. Wright's thesis is that Italy was a major influence on the American writers of fiction who visited that country.